Hesiod's Theogony : from Near Eastern creation myths to Paradise lost - Scully, Stephen (Oxford University Press, 2015)
This study both offers a reading of Hesiod's 'Theogony' and traces the reception and shadows of this authoritative Greek creation story in Greek and Roman texts up to Milton's 'Paradise Lost'. It also considers the poem in light of Near Eastern creation stories, including the 'Enûma Elish' and 'Genesis', as well as Freud's 'Civilization and Its Discontents'. In this book, Hesiod's poem is read as a hymn to Zeus and a city-state creation myth, arguing that Olympus is portrayed as an idealised polity and - with but one exception - a place of communal harmony